VD_FINDINFO Pron / 2015 / 19 vom 26. Juni 2015 - VD Tribunal cantonal (2015)
RETRAITVOIE DE DROIT, FRAIS JUDICIAIRES, DÉPENS, RÉDUCTIONEN GÉNÉRAL | 105 al. 2 CPC (CH), 106 al. 1 CPC (CH), 95 CPC (CH), 76 al. 2 TFJC (2010), 9 al. 1 TDC, 9 al. 2 TDC